Transversalidades: gênero e feminismos em diversidade e movimento - Paiva, Rosana Carvalho (Revista Estudos Feministas, 2016)
ASSIS, Gláucia de Oliveira; MINELLA, Luzinete Simões; FUNCK, Susana Bornéo (Orgs.) 1.ed.Entrelugares e Mobilidades. Tubarão, SC: Editora Copiart, 2014, 592p. (Desafios Feministas, Volume 3)